2021
DOI: 10.15376/biores.16.3.5508-5523
|View full text |Cite
|
Sign up to set email alerts
|

Optimizing methods to characterize caffeic, ferulic, and chlorogenic acids in Salicornia sinus-persica and Salicornia bigelovii extracts by tandem mass spectrometry (LC-MS/MS)

Abstract: Three types of phenolic acids (caffeic, ferulic, and chlorogenic acid) were identified and quantified in two halophytic plants (Salicornia bigelovii and Salicornia sinus-persica). Analysis was performed using a high-performance liquid chromatography-tandem mass spectrometry (HPLC-MS/MS) system via the standard addition method. The matrix effect (ME), recovery efficiency (RE), and process efficiency (PE) parameters were evaluated for S. bigelovii extracts, which revealed a strong ME on the ionization of the thr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 41 publications
0
4
1
Order By: Relevance
“…However, it is important to note that these extracts were obtained using 80% methanol, which significantly affects the final antioxidant properties. The antioxidant capacity determined by TEAC showed lower values than those reported by Cybulska et al [ 27 ] in polyphenol extracts of Salicornia sinus-persica and Salicornia bigelovii (1227 and 4795 μmol/g, respectively).…”
Section: Resultscontrasting
confidence: 73%
“…However, it is important to note that these extracts were obtained using 80% methanol, which significantly affects the final antioxidant properties. The antioxidant capacity determined by TEAC showed lower values than those reported by Cybulska et al [ 27 ] in polyphenol extracts of Salicornia sinus-persica and Salicornia bigelovii (1227 and 4795 μmol/g, respectively).…”
Section: Resultscontrasting
confidence: 73%
“…Significant content (up to 57.52% of total compounds) of flavonoids and flavonoid glycosides have been revealed in S. bigelovii and S. europaea extracts. Other studies reported in the literature have isolated rutin hydrate (10.05 mg/g dw) and catechin hydrate (1.17 mg/g dw) from S. europea [24,39,56].…”
Section: Flavonoidsmentioning
confidence: 99%
“…The same LC-MS/MS system, as for α -solanine and α -chaconine determination, was used for the determination of phenolic acids (PAs), including caffeic (CaA), chlorogenic (ChA), and ferulic (FA) acids, according to the method described by Cybulska et al [ 39 ]. Chromatographic separation was achieved on the analytical column Luna 3 µm C18 (150 mm × 2.0 mm I.D., Phenomenex Inc., Torrance, CA, USA) using 5 mM ammonium acetate in water (A) and methanol (B) as mobile phase in a gradient mode of elution: 0 min 50% B, 2.5 min 50% B, 3 min 100% B, and 3.5 min 100% B.…”
Section: Methodsmentioning
confidence: 99%